Semigrupo de Weierstrass e códigos AG bipontuais - Souza, Wagner Dias Alves de (2017)
In this work we study basics concepts of the algebraic geometry related to Algebraic Geometric Goppa codes theory (AG codes). We have seen how the calculation of the Weierstrass semigroup can be applied in obtaining the parameters of certain AG codes. In particular, we calculated the Weierstrass semigroup at two points on the curve Xq2r defined by afim equation yq + y = xq +1 over Fq2r, where r is a positive odd integer and q is a prime power, and construct a two-point AG code over Xq2r whose relative parameters are better than comparable one-point AG code. The main reference of this work was [8].